Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Berbasis Scientific Approach Pada Mata Pelajaran Administrasi Umum Semester Genap Kelas X OTKP di SMK Negeri 1 Jombang - Lia Hariski Rahmawati; Siti Sri Wulandari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
This research development od student activity sheets aims to(1) describe the results of developing students scientific approach based sheets on general administration subjects, (2) describe the feasibility of developed students scientific approach on the subject, (3) describe the learner response to the application development studensts scientific approach that has been developed on the subjects. In general Administration subjects for class X OTKP 1 students at SMK N 1 Jombang. This research is a development uses R&D (the research and development) research with 4-D model consisting of  4 stages, namely defining, designing, development and distributing. this research was conducted at 20 learners in class X OTKP 1 at in SMK Negeri 1 Jombang, the results of the validation of the LKPDoverall score of 86%. The validation from material expersts score is 85%. The  validation score of the linguist is 80 % and the validation of the graphic expert is 94% with very strong interpretation. So it can be conluded that the development students research scientific approach based sheets on general Administration subject  even semester at SMK Negeri 1 Jombang is declared fit to be used as teaching materials.